The Collateral Effect of COVID-19 on the Epidemiology of Airborne/Droplet-Transmitted Notifiable Infectious Diseases in Taiwan - Hung-Jen Tang; Chih-Cheng Lai; Chien-Ming Chao (MDPI AG, 2022)
This study was conducted to compare the number of cases of airborne/droplet-transmitted notifiable infectious disease (NID) between the pandemic period (defined as from January 2020 to December 2021) and the pre-pandemic period (defined as the period from January 2018 to December 2019). The annual case numbers of airborne/droplet-transmitted NIDs from 2018 to 2021 were collected for comparison. Fourteen airborne/droplet-transmitted NIDs including measles, rubella, pertussis, influenza with severe complications, invasive pneumococcal diseases (IPD), Q fever, mumps, meningococcal meningitis, varicella, legionellosis, invasive Haemophilus influenzae type b infection, hantavirus syndrome, TB, and multidrug-resistant TB (MDRTB), were included for the analysis. Overall, the annual case number of these 14 airborne/droplet-transmitted NID was 11,930, 12,747, 9477, and 8268 in 2018, 2019, 2020, and 2021, respectively, and the overall incidence was 50.3, 53.6, 39.8, 34.6 per 100,000 populations in in 2018, 2019, 2020, and 2021. The case number of influenza with severe complications had the largest reduction from the pre-pandemic period to the pandemic period, with a reduction of 3076 cases, followed by TB (−2904), IPD (−490), mumps (−292), measles (−292), pertussis (−57), MDRTB (−43), rubella (−35), Q fever (−20), varicella (−12), meningococcal meningitis (−5), invasive H. influenzae type B (−4). In contrast, the case number of legionellosis increased from 492 during the pre-pandemic period to 676 during the pandemic period. In addition, hantavirus syndrome also increased from zero cases during the pre-pandemic period to three during the pandemic period. In conclusion, the occurrence of most airborne/droplet-transmitted NIDs, including both domestic and imported cases in Taiwan, was lower during the pandemic period than during the pre-pandemic period.